Measuring the Success of Adoption and Acceptance of Technology in the Risky Environment: An Instrument Design - Khaleel Faaeq Al-Sammarraie, Munadil; K. Faieq, Alaa; Al-Qasa, Khaled (International Journal of Engineering and Technology, 2018)
Electronic Government (eG) has become a very important tool to serve the beneficiaries; therefore, it has received the attention of many Information System (IS) researchers.  Due to the importance of the IS successes, this paper identifies the emergence of a clear gap to measure the success of adoption and the acceptance of technology in unstable circumstances such as wars, conflicts and violence. Nowadays, the unsuitability issue is increasing remarkably. This paper expands on previous studies whose focus was on investigating the success of adopting electronic services in dangerous and unsecured countries in the world. Consequently, a need for a specific tool to measure the success of technology adoption and acceptance among the users in unstable and risky conditions has become urgent. Based on the findings, it can be confirmed that this instrument is reliable to measure the success of adoption and the acceptance of technology in risky environments.